Yeast Cell Death During the Drying and Rehydration Process - Rodriguez-Porrata, Boris; Carmona-Gutierrez, Didac; Lopez-Matinez, Gema; Reisenbichler, Angela; Bauer, Maria; Madeo, Frank; Cordero-Otero, Ricardo (IntechOpen, 2012)
None